2012
DOI: 10.1159/000343316
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Swelling-Activated Chloride Currents (ICL,swell) in the Regulatory Volume Decrease Response of Freshly Dissociated Rat Articular Chondrocytes

Abstract: Background/Aims: Articular chondrocytes dwell in an environment that is continuously changing its osmolarity as a consequence of mechanical loading, yet their volume regulation capabilities (RVD) are not fully understood. This work aimed to determine the osmotic sensitivity of freshly isolated rat chondrocytes, their RVD capabilities and to study the properties of any anion currents associated. Methods: Cell volume responses were determined by microscopy. Whole cell patch clamp was used to record ion currents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…In addition, ClC-3, ClC-4, and ClC-7 currents are sensitive to DIDS whereas ClC-2 and ClC-5 currents are resistant to DIDS (Li and Weinman, 2002;Parkerson and Sontheimer, 2004). In rat articular cartilages, there is mRNA expression of ClC-3 (Ponce et al, 2012). Two human (ClC-3 and ClC-7) and three rodent (ClC-3, ClC-4, and ClC-6) ClC transcripts have been detected using chondrocyte Affymetrix DNA microarrays (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ClC-3, ClC-4, and ClC-7 currents are sensitive to DIDS whereas ClC-2 and ClC-5 currents are resistant to DIDS (Li and Weinman, 2002;Parkerson and Sontheimer, 2004). In rat articular cartilages, there is mRNA expression of ClC-3 (Ponce et al, 2012). Two human (ClC-3 and ClC-7) and three rodent (ClC-3, ClC-4, and ClC-6) ClC transcripts have been detected using chondrocyte Affymetrix DNA microarrays (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, siRNA knockdown of ClC-7 attenuated the Cl 2 currents elicited by acidic pH solution, strongly supporting our conclusion that ClC-7 is the molecular basis for Cl 2 current in OUMS-27 cells. Recently it has been reported that TMEM16A is expressed in rat articular chondrocytes (Ponce et al, 2012). TMEM16A has been suggested to be the molecular correlate for Ca 21 -activated Cl 2 channels in airway epithelial cells, vascular smooth muscle cells, and interstitial cells of Cajal in the gastrointestinal tract (Huang et al, 2012 ] i $ 1 mM (Funabashi et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…This mainly because Ano1 is required for the generation of slow waves [25] and also because the recorded slow waves maintain their characteristics stably after several days in culture [26]. ANO1 has been previously related to cell division and regulatory volume decrease (RVD) [27][28][29]. Therefore, the expression of ANO1 in our system could be related to compensation of osmotic homeostasis after stress produced by the tissue disruption process needed to generate ICC primary cultures.…”
Section: Multiplexed Rt-pcr and Immunohistochemistrymentioning
confidence: 90%
“…Synthesis of high-affinity Cl − channel inhibitors, such as NS3728 [12], has facilitated insight in VRAC’s physiological role in cell cycle progression. A four-transmembrane protein, the Leucine-rich repeat-containing protein 8 (LRRC8), was recently identified as a main constituent of the VRAC current [32, 44]. …”
Section: Introductionmentioning
confidence: 99%